The Influence of Product Quality, Promotion, and Price on Consumer Purchasing Decisions of Mie Gacoan Food - Iqbal Yodan Pratama; Abriandi Abriandi (Dinasti Publisher, 2025)
This study aims to analyze the Influence of Product Quality, Promotion, and Price on Consumer Purchase Decisions of Gacoan Noodles. Using quantitative methods with questionnaires as research instruments. The research sample consisted of 103 Mie Gacoan consumers living in North Jakarta. The data collection technique used is the Likert Scale. Questionnaires are used as a data collection technique. The structural equation model analysis method was used in this study. The research design is causal and aims to test the direct influence and moderation effect between variables. The software used is SmartPLS 4 (Partial Least Square). The results in this study are that product quality and promotion have a positive and significant influence on consumer purchase decisions. Promotions have the most influence on consumer purchasing decisions, followed by product quality. Price has no significant influence on consumer purchasing decisions. The results of the coefficient of determination of the promotion variable have the highest score, so this study provides a reference for readers and food sellers to optimize the promotion of their products through various channels, such as social media, advertising, and relevant events. Effective promotion increases consumer awareness and interest in the company's products. In addition to promotion, product quality needs to be improved so that this research provides benefits to Mie Gacoan company owners and other entrepreneurs to improve the quality of their products to meet consumer needs and expectations.